(untitled) (Annual of the Faculty of Philosophy in Skopje, 2020)
The non-proliferation of nuclear weapons is a matter of policy and social responsibility for world peace, while the peaceful development of nuclear technology is a matter of freedom, sovereignty and equality of nations. It is known that the improvement and development of nuclear weapons in the Cold War era was a constant process. In this paper, the author addresses the reasons behind the development and introduction of certain types of nuclear weapons in the armament, which according to the development programs at that time it is classified as weapons with intensive initial nuclear radiation. The neutron weapons emerge in part as a consequence of the doctrines of nuclear countries in accordance with the classification of possible wars that would have taken place in that era. The logical consequence of such a situation was the limited nuclear war, in which the nuclear forces became not only the owners of nuclear weapons, but also its hostages. The vision was that in a match with limited nuclear strikes, the winner might be the side that has more sophisticated weapons at the moment. The neutron bomb, officially defined as a high-radiation weapon, is a low-performance thermonuclear weapon designed to maximize deadly neutron radiation in the immediate vicinity of an explosion while minimizing the physical power of the explosion itself. The question remains whether the spread of various and even partially inaccurate information that protection is very difficult, almost impossible, may have one additional motive for the production and spread of this weapon – to influence morality, the political situation and to exert psychological pressure, not only tо armed forces but also the population in general ?!